PENGARUH LINGKUNGAN SEKOLAH ISLAMI DAN TEMAN SEBAYA TERHADAP SIKAP TOLERANSI ANTARUMAT BERAGAMA SISWA KELAS X SMA MUHAMMADIYAH 4 DEPOK - Muhammad Alif Dwiki; Annisa Nurul; Saripudin; Muhammad Alfi Syahrin (Darussalam, 2026)
This study was motivated by the importance of strengthening students’ interreligious tolerance attitudes in educational settings as an effort to maintain social harmony in a multicultural society. Schools play a strategic role in character development through a conducive educational environment and positive social interactions. This study aimed to examine the influence of the Islamic School Environment and Peer Groups on the Interreligious Tolerance Attitudes of tenth-grade students at SMA Muhammadiyah 4 Depok. The study employed a quantitative approach using a correlational survey method. The population consisted of 90 students, with 58 valid respondents selected through questionnaire-based data collection using a five-point Likert scale. Data were analyzed using multiple linear regression with IBM SPSS Statistics. The analytical procedures included descriptive statistics, normality testing, multicollinearity testing, t-tests, F-tests, and coefficient of determination analysis. The findings revealed that the Islamic School Environment had a positive and significant effect on students’ interreligious tolerance attitudes (β = 0.347; p = 0.021). Meanwhile, Peer Groups showed a positive but statistically insignificant effect (β = 0.219; p = 0.085). Simultaneously, the Islamic School Environment and Peer Groups significantly influenced students’ interreligious tolerance attitudes (F = 10.920; p = 0.000), with a contribution of 28.4% (R² = 0.284). This study concludes that the Islamic School Environment is the most dominant factor in shaping students’ interreligious tolerance attitudes. The study contributes empirical evidence that a moderate, inclusive, and rahmatan lil ‘alamin-oriented Islamic school culture can serve as an effective strategy for fostering tolerance and strengthening character education among secondary school students.